Management of Dyslipidaemia in Real-world Clinical Practice: Rationale and Design of the VIPFARMA ISCP Project - Ricardo Lopez Santi; Felipe Martinez; Adrian Baranchuk; Alvaro Sosa Liprandi; Daniel Piskorz; Alberto Lorenzatti; Juan Carlos Kaski (European Cardiology Review)
Dyslipidaemia plays a major role in the pathogenesis of atherosclerosis. Every year, scientific institutions publish cardiovascular prevention guidelines with updated goals and recommendations based on new evidence. However, medical barriers exist that make achieving these goals difficult and gaps between guidelines and best daily clinical practice still persist. The International Society of Cardiovascular Pharmacotherapy designed the Surveillance of Prescription Drugs in the Real World Project (VIPFARMA ISCP), a survey for physicians who manage lipid disorders in high-risk patients. Seven clusters of questions will be analysed comprising demographics, institution profile, access to continuing medical education, clinical practice profile, attitude regarding use of statins, knowledge regarding proprotein convertase subtilisin/kexin type 9 inhibitors and attitudes regarding medical decisions about triglycerides. The present study will be the first part of a larger programme and aims to shed light on barriers between lipid-lowering drug therapy recommendations in the 2019 European Society of Cardiology guidelines and clinical practice in different countries.